Planning and performance measurement in higher education: three case studies of operational research application (2021)
ABSTRACT : In this work, we illustrate the application of a wide variety of Operations/operational research (OR) tools in higher education through three case studies based on practical applications conducted in the Engineering School of the Universidad de Antioquia. These case studies focus, respectively, on capacity planning, resource allocation, and performance measurement. In the first case study, we model and predict the flow of students enrolled in the industrial engineering program through the new curriculum using system dynamics and algebraic modeling of dropout rates, finding the number of sections for the courses, and the corresponding number of faculty positions needed to support the program structure. The second case study is a course covering model for the new curriculum that considers preferences and capacities of the teaching staff in an integer programming model, to find the uncovered courses of the new curriculum. Finally, the third case study presents a data envelopment analysis tool currently used to evaluate and rank the faculty of the Engineering School according to their teaching performance. The case studies presented in this work showcase how helpful OR tools are to rationalize the decision-making process in higher education institutions.